Billy and Blaze - Anderson, C. W. (Clarence William), 1891-1971 (New York, NY : Aladdin Paperbacks, 2000)
A little boy who loves horses gets a special birthday present.
Ages 5-8.
Keywords: Horses -- Juvenile fiction